IMPLEMENTASI MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA TENTANG CERITA FIKSI DI KELAS III SEKOLAH DASAR - Kurniasih, Dedeh; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the implementation of the Cooperative Script learning model in improving the writing skills of fiction stories among third-grade elementary school students, involving two classes as samples, namely class III A (25 students) and class III B (23 students). This research uses a quantitative approach with a quasi-experimental design, where class III A is the experimental group implementing the Cooperative Script model, while class III B is the control group using conventional learning methods. The instrument used in this study is a fiction writing test, which includes language aspects, story structure, and creativity, analyzed using a writing quality assessment scale. The data obtained were analyzed using a t-test to test the significance of the differences between pre-test and post-test scores in each group. The results show a significant improvement in the fiction writing skills of students taught using the Cooperative Script model. The average post-test score of the experimental group was higher compared to the control group, indicating that the Cooperative Script learning model is effective in improving the fiction writing skills of third-grade elementary school students. These findings provide evidence that the use of the Cooperative Script model can be an effective alternative to enhance writing skills in elementary schools.